2013
DOI: 10.1158/0008-5472.can-12-3055
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation-Mediated Repression of miR-886-3p Predicts Poor Outcome of Human Small Cell Lung Cancer

Abstract: Small cell lung cancer (SCLC) is one of the most aggressive types of cancer, yet the pathologic mechanisms underlying its devastating clinical outcome remain elusive. In this report, we surveyed 924 miRNA (miR) for their expressions in the formalin-fixed paraffin-embedded specimens from 42 patients with SCLC, and found that the downregulated miR-886-3p is closely correlated with the shorter survival of SCLC. This correlation was validated with another 40 cases. It was further discovered that loss of miR-886-3p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
131
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(151 citation statements)
references
References 48 publications
19
131
0
1
Order By: Relevance
“…They discovered that lower miR-150 and miR-886-3p expression levels were associated with a poor OS and PFS. These findings retained statistical significance as independent predictors of survival after adjusting for age, gender and smoking status and confirmed the results of a previous study on the prognostic role of miR-886-3p levels in SCLC (Cao et al 2013). In that study, miR.886-3p expression was found to be regulated by DNA promoter methylation and to potentially repress cell proliferation, migration and invasion.…”
Section: Mirnas As Prognostic Markers In Neuroendocrine Tumorssupporting
confidence: 89%
“…They discovered that lower miR-150 and miR-886-3p expression levels were associated with a poor OS and PFS. These findings retained statistical significance as independent predictors of survival after adjusting for age, gender and smoking status and confirmed the results of a previous study on the prognostic role of miR-886-3p levels in SCLC (Cao et al 2013). In that study, miR.886-3p expression was found to be regulated by DNA promoter methylation and to potentially repress cell proliferation, migration and invasion.…”
Section: Mirnas As Prognostic Markers In Neuroendocrine Tumorssupporting
confidence: 89%
“…Effectively, in human cancer cell lines, DNA methylation has been shown to modulate the miR-886-3p expression [41]. Moreover, miR-886-3p and the pre-miR-886 can strongly repress cell proliferation [23,41]. We found that pre-miR-886 was also responsible for the regulation of cell proliferation in CD4 + T-cells.…”
Section: Discussionmentioning
confidence: 70%
“…We showed also that the DNA methylation of this region could control the VTRNA2-1 expression level in CD4 + T-cells. Effectively, in human cancer cell lines, DNA methylation has been shown to modulate the miR-886-3p expression [41]. Moreover, miR-886-3p and the pre-miR-886 can strongly repress cell proliferation [23,41].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs have been reported as targets of epigenetic events during carcinogenesis. In lung cancer, several miRNAs, such as miR-9-3, miR34b, miR-124-1, miR-124-2, miR-124-3, mir-126, miR-137, miR-152, miR-193a, miR-503, and miR-886-3p, are silenced by DNA hypermethylation [33][34][35][36][37][38][39][40][41]. Furthermore, histone modification may be another possible epigenetic mechanism underlying aberrant miRNA expression.…”
Section: Introductionmentioning
confidence: 99%